2022
DOI: 10.1152/ajpcell.00414.2021
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acid treatment of mouse preimplantation embryos demonstrates contrasting effects of palmitic acid and oleic acid on autophagy

Abstract: Treatment of mouse preimplantation embryos with elevated palmitic acid (PA) reduces blastocyst development, while co-treatment with PA and oleic acid (OA) together rescues blastocyst development to control frequencies. To understand the mechanistic effects of PA and OA treatment on early mouse embryos, we investigated the effects of PA and OA, alone and in combination, on autophagy during preimplantation development in vitro. We hypothesized that PA would alter autophagic processes and that OA co-treatment wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Also, impaired FA metabolism coincides with high fat diet-associated ovarian dysfunction 18 . Exposure of cultured early embryos to speci c FA revealed that palmitic acid (PA) slowed developmental progression and induced autophagy, while OA reversed those responses 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, impaired FA metabolism coincides with high fat diet-associated ovarian dysfunction 18 . Exposure of cultured early embryos to speci c FA revealed that palmitic acid (PA) slowed developmental progression and induced autophagy, while OA reversed those responses 19 .…”
Section: Introductionmentioning
confidence: 99%